Diagnostic Accuracy of Procalcitonin in Bacterial Meningitis Versus Nonbacterial Meningitis: A Systematic Review and Meta-Analysis - Wei, Ting-Ting; Hu, Zhi-De; Qin, Bao-Dong; Ma, Ning; Tang, Qing-Qin; Wang, Li-Li; Zhou, Lin; Zhong, Ren-Qian (Medicine (Baltimore), 2016)
Several studies have investigated the diagnostic accuracy of procalcitonin (PCT) levels in blood or cerebrospinal fluid (CSF) in bacterial meningitis (BM), but the results were heterogeneous. The aim of the present study was to ascertain the diagnostic accuracy of PCT as a marker for BM detection. A systematic search of the EMBASE, Scopus, Web of Science, and PubMed databases was performed to identify studies published before December 7, 2015 investigating the diagnostic accuracy of PCT for BM. The quality of the eligible studies was assessed using the revised Quality Assessment for Studies of Diagnostic Accuracy method. The overall diagnostic accuracy of PCT detection in CSF or blood was pooled using the bivariate model. Twenty-two studies involving 2058 subjects were included in this systematic review and meta-analysis. The overall specificities and sensitivities were 0.86 and 0.80 for CSF PCT, and 0.97 and 0.95 for blood PCT, respectively. Areas under the summary receiver operating characteristic curves were 0.90 and 0.98 for CSF PCT and blood PCT, respectively. The major limitation of this systematic review and meta-analysis was the small number of studies included and the heterogeneous diagnostic thresholds adopted by eligible studies. Our meta-analysis shows that PCT is a useful biomarker for BM diagnosis.